2021
DOI: 10.3390/mps4020033
|View full text |Cite
|
Sign up to set email alerts
|

Using the Veggie Meter in Elementary Schools to Objectively Measure Fruit and Vegetable Intake: A Pilot Study

Abstract: Self-reported fruit and vegetable (FV) consumption in children has limitations that could be overcome with objective measures that are easy to implement. The Veggie Meter (VM) is a non-invasive portable device that measures skin carotenoid levels, a concentration biomarker of usual FV intake. While VM has been used to measure FV consumption in adults, few studies have explored its use in elementary school settings. Designing research studies using the VM with elementary school-age children requires an understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 40 publications
2
30
1
Order By: Relevance
“…While dietary intake was only assessed by proxy using the Veggie Meter ® , this was by design, as the Veggie Meter ® has been previously validated against several different criteria [43], and it was critical to determine if it can be successfully implemented in lowincome schools despite the logistical challenges that accompany working in this setting. Overall, this study supports the growing body of literature that suggests that the Veggie Meter ® is an appropriate tool for measuring change in fruit and vegetable consumption by proxy in the school setting, especially in a low-income school setting [24][25][26].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While dietary intake was only assessed by proxy using the Veggie Meter ® , this was by design, as the Veggie Meter ® has been previously validated against several different criteria [43], and it was critical to determine if it can be successfully implemented in lowincome schools despite the logistical challenges that accompany working in this setting. Overall, this study supports the growing body of literature that suggests that the Veggie Meter ® is an appropriate tool for measuring change in fruit and vegetable consumption by proxy in the school setting, especially in a low-income school setting [24][25][26].…”
Section: Discussionsupporting
confidence: 79%
“…With these considerations in mind, reflection spectroscopy has emerged as a relatively low-cost, non-invasive, and most-importantly, objective method of detecting changes in dietary behavior, specifically consumption of carotenoid-containing fruits and vegetables [24][25][26][27]. When consumed, carotenoids are deposited in the skin; greater consumption of fruits and vegetables is associated with higher amounts of detectable skin carotenoids [28].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation into the correlation between V/F intake and VM scores in children has not fully been proven. Martinelli et al [ 32 ] showed a significant positive relationship between vegetable intake and VM scores, but not between green vegetable and fruit intake and VM scores. May et al [ 33 ] showed no correlation between vegetable intake and VM scores.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements are displayed as a Veggie Meter (VM) score (arbitrary unit). It has been confirmed that the VM can be used in public health studies as well as studies with preschool and school children [ 30 , 31 , 32 , 33 , 34 ], where the validity was ensured through the associations between RS measures and dietary carotenoids, V/F intake as calculated from a validated food frequency questionnaire, and plasma carotenoids [ 35 , 36 ]. Thus, quantifying V/F intake using a VM can raise dietary awareness and may promote the efficiency of dietary education even in children.…”
Section: Introductionmentioning
confidence: 99%
“…Skin carotenoids measured by RRS were strongly correlated (r = 0.62, p < 0.001) with both serum and plasma carotenoids. While Martinelli et al [29] applied Veggie Meter (VM), a widely used RS device, to assess skin carotenoids, they only found weak correlations (r = 0.174, p = 0.042) between total vegetable consumption and VM scores. For the fruit group, no significant correlations were observed.…”
Section: Skin Biomarkersmentioning
confidence: 99%